Electrical Resistivity of a Partially Saturated Porous Medium at Subzero Temperatures - Herring, T. (2020)
This study used a unique laboratory apparatus to collect electrical resistivity tomography data for a uniform porous medium at temperatures from −20 to 25°C for a range of initial water saturations. Archie's equation was modified to include the effects of temperature above and below 0°C. Resistivity data collected below 0°C were used to estimate temperature‐dependent liquid water saturation and fluid resistivity. The amount of unfrozen water remaining at a given temperature was not related to initial water saturation and was nearly identical for all initial saturations at temperatures below about −5°C. The dependence of resistivity–temperature curves on initial water saturation at subzero temperatures was caused by differences in fluid resistivity as a result of ion exclusion during freezing. The relationships established in this study provide insight into the physical mechanisms that govern the resistivity of porous media at subzero temperatures and a starting point for quantitative analysis of resistivity data collected in frozen ground.